Evaluasi Kualitas Tanah dan Arahan Pengelolaan Tanah Sawah Berbasis Sistem Informasi Geografis di Kecamatan Sidemen - Silitonga, Septia Ningsih; Arthagama, I Dewa Made; Soniari, Ni Nengah (Agrotrop : Journal on Agriculture Science, 2024)
Evaluation of Soil Quality and Directions for Paddy Field Management Based on Geographic Information Systems in Sidemen District. Soil quality assessment is a crucial component of agricultural land management, as it provides valuable information about the condition of soil and its limiting factors, which in turn influences crop productivity and sustainability. Understanding the quality of soil is essential for making informed decisions related to land management practices, such as fertilization, irrigation, and crop rotation, to optimize agricultural production and protect the environment. The research was conducted in agricultural lands Sidemen District, Bali Province. The aim of the study was to analyse the physical, chemical, and biological factors to evaluate the spatial distribution of soil quality. Method for this research is integrated for Geographic Information System, field survey, laboratory soil analysis, and quantification soil quality based on Lal (1994). Soil quality indicators, such as soil texture, unit weight, porosity, moisture content, field capacity, pH, C-organic, CEC, base saturation, nutrients (N, P, and K), and C-biomass, were measured as a minimum data set (MDS). This study showed that the soil quality have a moderate to good category. The limiting factors in the study area encompassed texture, water content, N, P, and C-biomass. The proposed land management recommendations include utilizing tractors and implementing organic fertilizers, urea, and SP-36 in the paddy fields of the Sidemen District.